Determinan Kepemimpinan - Runtu, Bob Wawo (Makara Human Behavior Studies in Asia, 2003)
The purpose of this research is to look for determinants that effect leadership. The research was conducted in 13 airports and in the head office of its managing organization consisting of 84 different working units on different levels. The sample size is 3.048 respondents from a total of 4.150 employees. The findings are 22 hypotheses explaining leadership significantly: 16 independent variables determine positively and show a mutual impact as well as an accumulative direct influence to and from leadership. Only one variable shows a positive impact on leadership without any impact back. Five variables show a negative and non-accumulative effect towards leadership. Determinants show to have a positive, mutual and accumulative direct impact towards leadership. These determinants are: conduct to change, communication, working with leadership, networking, developing human resources, influence, working in groups, managing differences, using local language, commitment, discipline, non-reward based working, optimism, mutual caring, and consistency. One determinant, leader using software other than MS Office has a positive effect towards leadership. However, leadership has no impact on the use of software other than MS Office towards the leader. The other 5 variables show a negative, non-mutual and non-accumulative impact towards leadership, these variables are: happiness, perseverance, efficiency, serving others with respect, and adherence to norms.